البصمة الوراثية في الاثبات - Abdul Latif; Abdalkreem ibnu Saad Salih Al Yahya (Pascasarjana IAIN Metro, 2023)
In this research, I dealt with what DNA is, through its definition and characteristics, and touched on the uses of DNA in the field of pedigree and the conditions for working with DNA to ensure its results. It provided the legal and technical conditions. It also dealt with proving and pure lineage by DNA, and then explained the legality of taking the fingerprint from the accused without his consent. And the adequacy of using DNA as evidence of guilt. It also becomes clear to us at the end of this research: that whenever the charges are unable to prove the opposite of the charge attributed to him with stronger evidence than the fingerprint presented against him, then the fingerprint must be relied upon in the crimes that the perpetrator is accused of, and this is left to the criminal judge, but in those crimes as crimes Borders and retaliation, so it is not permissible to rely on the genetic fingerprint, because the legal ruling by itself has been shown, and that is when it is considered a form of. Pictures of the evidence, including legally and legally. Likewise, the Saudi judiciary does not object to conducting a DNA examination, even without the consent of the accused, as it ruled that there is no legal objection to relying on the DNA in aesthetic investigation, and considering it as a means, and accordingly we reached the following results: The DNA plays an important role in aesthetic proof, as it is one of physical evidence It is considered a strong presumption in the conviction or innocence of the accused, but it is not permissible to rely on it alone except in reinforcement crimes. There is a need for safeguards in the laboratory environment to ensure the integrity and accuracy of DNA processing at all times. If the trials of the case and the investigation call for the use of DNA to achieve justice, it will be done. Taken from the accused if without his consent. There must be legal guarantees in the conditions for resorting to DNA testing and protecting it from Illegal use.